Dermoscopy of very small basal cell carcinoma (≤3 mm) - Camilo Arias-Rodriguez; Ana Maria Muñoz-Monsalve; Diana Cuesta; Susana Mejia-Mesa; Maria Soledad Aluma-Tenorio (Anais Brasileiros de Dermatologia, 2023)
Abstract Background Basal cell carcinoma (BCC) dermoscopy is key to lower the biopsy threshold of suspicious lesions. There is a scarcity of published data on the dermoscopy of very small BCC (≤3 mm) and its differences from larger BCCs. Objective To describe and compare dermoscopic features of BCCs measuring ≤3 mm, with those from 3 to 10 mm. Methods An analytical cross-sectional study, included biopsy-proven BCCs that had dermoscopic photographic images, between January 2017 and December 2022 in a Skin Cancer Center in Medellín, Colombia. Demographic, clinic-pathological and dermoscopic features were compared between very small BCCs (vsBCCs) and a reference group. Results A total of 326 BCCs in 196 patients were included, of whom 60% were male. The most common Fitzpatrick phototype was III. vsBCCs accounted for 25% of the lesions (81/326). Face and neck were the most frequent locations (53%), especially in very small tumors. The nodular type was more common in very small tumors than in larger lesions, the superficial type was less frequent, and aggressive types were equally prevalent in both groups. On dermoscopy, very small tumors were statistically more likely to present pigmented structures than reference lesions, especially blue-gray dots (67% vs. 54%), vessels were less frequent, particularly short-fine telangiectasias (SFT) (52% vs. 66%), as were other structures such as shiny white structures (SWS), ulceration, micro-erosions, and scales. Study limitations Latin-American sample, lacks information on dark phototypes Conclusions Pigmented structures, especially blue-gray dots, were most common in vsBCCs when compared to larger lesions; SFT, SWS and other findings were less prevalent.